Sistem Informasi Penjualan (E-Commerce) Pakaian Jadi Pada Nuansa Fashion Dengan Menggunakan Bahasa Pemrograman PHP dan Database Mysql - Hanafi; Arief; Prawiro (Riset Sinergi Indonesia (RISINDO), 2023)
Research has been carried out on the Nuansa Fashion with the aim of developing an information system that has seemed uninformative. And from the research that was conducted, it was found some shortcomings of the old system which still uses many manual methods. From the shortcomings found, a system development can be recommended. Where in this case by using the PHP Database and MySQL Application as a system design programming language that has been commonly known among programmers. In addition, the development of this system is also supported by several references relating to several references relating to the topics discussed. The purpose of this development is later to be able to improve performance in processing data and improve the quality of information produced which can be used as a leader as a guide in making a decision for the progress of the organization he leads.